Echocardiographic parameters of the left ventricle in patients after Q-wave and non-Q-wave myocardial infarction - V. E. Oleynikov; L I. Salyamova; A. V. Golubeva; O. D. Vershinina; A. A. Chernova; N. A. Donetskaya (Российский кардиологический журнал)
Aim. To perform a dynamic assessment and comparative analysis of non-invasive parameters of myocardial function in patients with Q-wave and non-Q-wave myocardial infarction (MI) during 24-week follow-up after revascularization.Material and methods. A total of 95 patients with acute MI were included. On days 7-9 and after 24 weeks, speckle tracking echocardiography was performed with assessment of global longitudinal (GLS), global circumferential (GCS) and global radial strain (GRS), global work index (GWI), global constructive work (GCW), global wasted work (GWW), global work efficiency (GWE).Results. Taking into account the presence/absence of the Q wave, the subjects were divided into two groups: Q-wave MI — 66 patients (69,5%), non-Q-wave MI — 29 (30,5%) people. In the Q-wave MI group, by the 24th week, most parameters of myocardial performance were significantly lower than in the comparison group. In group 1, GWE was 93 (87; 96)% vs 96 (91; 97)% (p=0,04) in group 2; GWI — 1429±444,1 and 1653,3±385,84 mm Hg %, respectively (p=0,02). The GCW level in the Q-wave MI group was 1640±477,8 mm Hg % vs 1852,9±440,88 mm Hg % in the non-Q-wave MI group (p=0,04). Subsequently, a favorable increase in GLS (p=0,01), GWI (p=0,04), GWE (p=0,01), GCW (p=0,03) was revealed in the non-Q-wave MI group.Conclusion. The results obtained suggest that non-invasive parameters of myocardial performance can be used to assess transient ischemic dysfunction due to myocardial stunning, expressed to varying severity in patients with Q-wave MI and non-Q-wave MI.